2008
DOI: 10.1177/0003319708325443
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atherosclerotic Indicators between Cardio Ankle Vascular Index and Brachial Ankle Pulse Wave Velocity

Abstract: As a means of estimating the extent of atherosclerosis in large arteries, our results show that both brachial ankle pulse wave velocity and cardio ankle vascular index are useful and that cardio ankle vascular index may have some advantages in its application to patients taking blood pressure-lowering medication because of the minimum effect of blood pressure on its measurement values. The cardio ankle vascular index has increased performance over brachial ankle pulse wave velocity in predicting the coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 26 publications
0
60
0
5
Order By: Relevance
“…Izuhara et al 25) reported that CAVI is indepen- , Izuhara 25) , Miyoshi 26) , Horinaka 27) [Sairaku 29) ] Intima media thickness of cervical artery Nakamura 24) , Ibata 22) , Takaki 20,28) , Izuhara 25) , Miyoshi 26) , Okura 36) , Sairaku 29) , Horinaka 27) , Hayashi 38) Chronic kidney disease [Mortality rate in patients with hemodialysis] Izuhara 25) , Kobuzono 30) , Takenaka 31) , Nakamura 32) , Ueyama 33) , Satoh-Asahara 36) [Kato 40) ] Cerebral infarction, Dementia Yamamoto 39) Metabolic syndrome Satoh 55) Diabetes mellitus Ibata 22) , Izuhara 25) , Okura 37) Hypertension Kubozono 21) , Okura 37) , Takaki 42) , Kadota 43) Dyslipidemia Takaki 28) Smoking Kubozono 21) , Noike 62) Obstructive sleep apnea syndrome Kumagai 60) dently associated with the severity of coronary atherosclerosis. Recently, Miyoshi et al 26) also supported a correlation between CAVI and coronary atherosclerosis.…”
Section: A Coronary Artery Diseaseunclassified
“…Izuhara et al 25) reported that CAVI is indepen- , Izuhara 25) , Miyoshi 26) , Horinaka 27) [Sairaku 29) ] Intima media thickness of cervical artery Nakamura 24) , Ibata 22) , Takaki 20,28) , Izuhara 25) , Miyoshi 26) , Okura 36) , Sairaku 29) , Horinaka 27) , Hayashi 38) Chronic kidney disease [Mortality rate in patients with hemodialysis] Izuhara 25) , Kobuzono 30) , Takenaka 31) , Nakamura 32) , Ueyama 33) , Satoh-Asahara 36) [Kato 40) ] Cerebral infarction, Dementia Yamamoto 39) Metabolic syndrome Satoh 55) Diabetes mellitus Ibata 22) , Izuhara 25) , Okura 37) Hypertension Kubozono 21) , Okura 37) , Takaki 42) , Kadota 43) Dyslipidemia Takaki 28) Smoking Kubozono 21) , Noike 62) Obstructive sleep apnea syndrome Kumagai 60) dently associated with the severity of coronary atherosclerosis. Recently, Miyoshi et al 26) also supported a correlation between CAVI and coronary atherosclerosis.…”
Section: A Coronary Artery Diseaseunclassified
“…In patients with risk factors such as hypertension, diabetes, hypercholesterolemia 4,5) , obesity 6) and smoking 7) , the CAVI values are higher than in controls. A high CAVI score is associated with carotid and coronary atherosclerosis [8][9][10] and is better at predicting coronary artery disease than brachial ankle pulse wave velocity (ba-PWV) 11,12) . Thus, the CAVI method is a useful tool for screening people with moderate to advanced levels of atherosclerosis 13) .…”
Section: Office Blood Pressurementioning
confidence: 99%
“…8,[19][20][21][22][23] After examinations had been performed on the right and left sides, the lower ankle-brachial pressure index and the higher CAVI were selected for analyses. Ankle-brachial pressure index o0.9 was considered as indicative of peripheral arterial disease.…”
Section: Measurement Of Ankle-brachial Pressure Index and Cavimentioning
confidence: 99%
“…2,10-12 Indeed, SBI is related to arteriolosclerosis such as lipohyalinosis and microatheroma, while WMHs are associated with the extravasation of toxic plasma constituents into the cerebral parenchyma due to endothelial dysfunction. [8][9][10][11][12] Finally, CAVI is independent of blood pressure because of the adjustment of blood pressure based on a stiffness parameter b, which is an index of local stiffness of a blood vessel, [20][21][22][23] and the stiffness parameter b may not be associated with WMHs. In the present study, both hypertension and age were independently associated with WMHs, which is consistent with observations from previous reports.…”
Section: Arterial Stiffness and Silent Brain Infarct N Saji Et Almentioning
confidence: 99%
See 1 more Smart Citation